Resource reservation based on relaxed policy for grid workflow - Peng XIAO; Zhi-gang HU; Chao-kun YAN; Xi-long QU (Tongxin xuebao)
To address the problem that applications tend to overestimate reservation duration,a novel reservation technique based on overlapping relaxing policy was proposed,so as to mitigate the negative effects of stringent reservation mechanisms on system performance.The analysis of the relaxed policy was represented theoretically and a relaxed admission algorithm was designed for large-scale grid workflows.Experimental results show that relaxed policy can significantly mitigate the negative effects of classical policies when system is in presence of heavy workload.Experimental results based on a real workflow indicate that the relaxed policy is able to decreasing the efficiency loss due to the overestimation of reservation durations.